PHOTONIC CURING OF SNO2 ELECTRON TRANSPORT LAYER FOR LARGE-SCALE PRODUCTION OF FLEXIBLE PEROVSKITE SOLAR CELLS - Muratov, Adilet (Nazarbayev University School of Sciences and Humanities, 2025)
Intense pulse light (IPL) annealing is a rapid annealing approach that can sinter materials within ultrashort duration by discharging energetic light pulses, typically from a xenon lamp. IPL annealing optimization for SnO2 electron transport layer was conducted and several characterizations were performed. The two-step annealing, ink drying on hot plate at 100°C for 5 min followed by a single pulse with the voltage 2400 V and duration 1000 μs, was found to be the optimal setting that allowed to achieve comparable values for sheet resistance, conductivity, hall mobility, and charge extraction capability to 130°C for 30 min hot plate annealing. Furthermore, it was confirmed that the IPL annealed SnO2 layer is a suitable platform for perovskite layer formation.
Keywords: Optoelectronics; Flexible Printed Perovskite Solar Cells; Intense pulsed light annealing; Electron Transport Layer; Tin(IV) oxide; type of access: embargo